1991
DOI: 10.1177/089686089101100211
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Toxicity Due to Gentamicin in Peritoneal Dialysis Patients

Abstract: Gentamicin is well known to be a cause of vestibular toxicity. Despite this, gentamicin is often used to treat peritonitis and exit site infections in peritoneal dialysis patients because of the ease of intraperitoneal administration and the broad coverage of aerobic Gram-negative bacilli, including Pseudomonas aeruginosa. We report 4 cases of severe vestibular toxicity occurring in peritoneal dialysis patients treated with gentamicin. They were all treated as outpatients for peritonitis or an exit-site infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…256,257 Not unexpectedly, ototoxicity occurs with IP aminoglycosides, similar to systemic administration, as confirmed in both animal models 258 and human. 259,260 According to an observational study of PD patients, risk factors for hearing loss include older age, episodes of peritonitis and cumulative doses of amikacin and vancomycin. 166 The mechanism of aminoglycoside ototoxicity is incompletely understood.…”
Section: Dosage Of Antibioticsmentioning
confidence: 99%
“…256,257 Not unexpectedly, ototoxicity occurs with IP aminoglycosides, similar to systemic administration, as confirmed in both animal models 258 and human. 259,260 According to an observational study of PD patients, risk factors for hearing loss include older age, episodes of peritonitis and cumulative doses of amikacin and vancomycin. 166 The mechanism of aminoglycoside ototoxicity is incompletely understood.…”
Section: Dosage Of Antibioticsmentioning
confidence: 99%
“…24 Indeed, this suspicion has been supported by a clinical study 18 (Table 1) and a case report of 4 patients with aminoglycoside-induced vestibular injury from intraperitoneal administration alone. 33 Gendeh et al 18 found a very high incidence of vestibular injury in patients receiving repeated courses of aminoglycosides for peritoneal dialysis-related peritonitis. Clearly, the little evidence that is available does not suggest that intraperitoneal administration minimizes this risk.…”
Section: Risk Factorsmentioning
confidence: 99%
“…101 For people who receive gentamicin and renal dialysis concurrently, it is estimated that the likelihood of sustaining BVH is from 12.5% to 30%. 102,103 Unfortunately, it appears that people who are susceptible to ototoxicity have little protection from monitoring serum levels of these antibodies. 104 Less common causes of BVH include meningitis, head trauma, tumors on each eighth cranial nerve (including bilateral vestibular schwannoma), transient ischemic episodes of vessels supplying the vestibular system, and sequential unilateral vestibular neuronitis.…”
Section: Bilateralmentioning
confidence: 99%